The Department of Veterans Affairs Biorepository Brain Bank: A national resource for amyotrophic lateral sclerosis research. Issue 7 (December 2013) - Brady, Christopher B.; Trevor, Katrina T.; Stein, Thor D.; Deykin, Eva Y.; Perkins, Sally D.; Averill, James G.; Guilderson, Latease; Mckee, Ann C.; Renner, Stephen W.; Kowall, Neil W.
Abstract: Our objective was to describe a unique national resource to facilitate amyotrophic lateral sclerosis (ALS) research, the Department of Veterans Affairs Biorepository Brain Bank. Enrolled veterans receive biannual telephone follow-up to collect clinical data until death including the ALS Functional Rating Scale-Revised (ALSFRS-R). A comprehensive post mortem examination is performed and a wide range of fixed and frozen brain and spinal cord samples are banked. As of December 2012, 240 veterans were enrolled from 47 states and post mortem tissue recoveries were performed on 100 veterans from 37 states. Average disease duration was 13.5 (range 3−45) years. Average follow-up for living subjects was 3.1 years and average ALSFRS-R score was 23.5 compared to 25.9 (12−24 months earlier), indicating slow disease progression. ALS was confirmed by post mortem examination in 97% of cases. Eighty-six percent of cases were TDP-43-positive. Additional neuropathological diagnoses include Lewy body disease (13%), frontotemporal lobar degeneration (6.3%), chronic traumatic encephalopathy with motor neuron disease (3.2%), and Alzheimer's disease (2.1%). Tissue RIN values were ≥ 4.0 in 88% of cases. In conclusion, the availability of high quality fixed and frozen CNS tissue from this well characterized cohort is an important resource to facilitate research into genetic and environmental risk factors and clinical pathological relationships in ALS.